2016
DOI: 10.1007/s10597-015-9972-3
|View full text |Cite
|
Sign up to set email alerts
|

US Veterans’ Court Programs: An Inventory and Analysis of National Survey Data

Abstract: This study used data from a phone survey inventory of US veterans' courts to provide descriptive information on the current status of their various elements. To identify which items were most predictive of a court's percentage of subjects terminated from their program, a linear regression was performed. The following were associated with higher rates of termination from the veterans' court (VC) program: (a) programs that offered phase progression based on measurable goals, (b) programs that conduct frequent dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…However, the level of association was no longer significant after the Bonferroni adjustment was applied. Prior research has shown that 55% of VC programs utilize behavioral contracts (16).…”
Section: Resultsmentioning
confidence: 99%
“…However, the level of association was no longer significant after the Bonferroni adjustment was applied. Prior research has shown that 55% of VC programs utilize behavioral contracts (16).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of VTC programs include a mentoring component (Johnson et al, 2016), and mentoring has been a component of VTCs since their inception. The first sustained VTC in Buffalo, New York, incorporated volunteer veteran mentors into the court's structure.…”
Section: Mentors In Vtcsmentioning
confidence: 99%
“…These courts, like other specialty courts, grew out of individual communities and are often reflective of the style of their judicial leaders. They may differ in their clinical and legal eligibility requirements, whether they are post‐plea or pre‐plea, and the types of sanctions and rewards meted out (Johnson et al, ), yet through the efforts of Justice for Vets and with the support of the National Association of Drug Court Professionals, court staff training provides consistency and a goal of conforming to the basic principles of drug courts (Justice for Vets, n.d.‐b). Critical VTC elements include a non‐adversarial approach, mental health treatment and availability of support services, judicial accountability through close monitoring, and consistent use of rewards and sanctions to modify participant behavior.…”
Section: How Veteran Treatment Courts Workmentioning
confidence: 99%
“…A criminal record will compound these challenges by adding further barriers to employment and housing, and by increasing disruption to family and support systems. The VTC model allows a shift in focus from a punitive to a rehabilitative stance, taking advantage of the vocational, educational, and housing benefits that veterans have earned through their military service, and by providing for the possibility of reduction or dismissal of charges (Johnson et al, ). Additionally, VTCs offer an opportunity to connect veterans to community services and support, such as through peer mentor programs that have been established in the VA (Oh & Rufener, ) and have become a component of VTC programs (Justice for Vets, n.d.‐d).…”
Section: Ethical Justificationmentioning
confidence: 99%
See 1 more Smart Citation